2018
DOI: 10.1177/1524838018767933
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Victimization and Mental Illness Prevalence Rates Among Incarcerated Women: A Literature Review

Abstract: Incarcerated women evidence high rates of both interpersonal trauma and mental illness. In particular, the rates of sexual violence victimization are so high that some researchers have suggested that sexual abuse may be a pathway to prison for women, likely through the development of mental illness, including substance abuse. This review article summarizes the literature on sexual victimization ( n = 32 articles; 28 independent studies) and mental illness ( n = 11 articles; 8 independent studies) prevalence am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 85 publications
3
104
0
4
Order By: Relevance
“…Adjusting to being incarcerated can be stressful, possibly even traumatic, and women with histories of sexual assault struggle with adjustment more so than do women without sexual assault histories (Islam-Zwart & Vik, 2004 ; Yardley & Wilson, 2013), although the concern that prisons are necessarily chronically stressful is likely overstated (Bonta & Gendreau, 1990). Because most women who are incarcerated have a history of prior trauma exposure (Karlsson & Zielinski, 2018), incorporating trauma treatments into therapeutic programming in prison settings is a priority (Hall et al, 2013). However, there are questions about whether it is appropriate to offer such treatment to women at all, especially when the treatments use exposure techniques which necessitate the retelling of traumatic, intrusive memories at a time and in a place where women may be feeling especially vulnerable (Miller & Najavits, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjusting to being incarcerated can be stressful, possibly even traumatic, and women with histories of sexual assault struggle with adjustment more so than do women without sexual assault histories (Islam-Zwart & Vik, 2004 ; Yardley & Wilson, 2013), although the concern that prisons are necessarily chronically stressful is likely overstated (Bonta & Gendreau, 1990). Because most women who are incarcerated have a history of prior trauma exposure (Karlsson & Zielinski, 2018), incorporating trauma treatments into therapeutic programming in prison settings is a priority (Hall et al, 2013). However, there are questions about whether it is appropriate to offer such treatment to women at all, especially when the treatments use exposure techniques which necessitate the retelling of traumatic, intrusive memories at a time and in a place where women may be feeling especially vulnerable (Miller & Najavits, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because many survivors of sexual assault, who are most often women, commonly use drugs and/or alcohol to cope with posttraumatic symptoms (Ullman et al, 2013), greater enforcement of drug laws disproportionately increases women's justice involvement. Indeed, a recent review found that 56% to 82% of incarcerated women have experienced lifetime sexual victimization, with 50% to 66% having experienced sexual abuse in childhood (karlsson & Zielinski, 2018).…”
Section: Trauma Exposure In Incarcerated Womenmentioning
confidence: 99%
“…Over half of people who are incarcerated meet criteria for at least one mental illness (Fazel & Danesh, 2002 ; Fazel, Yoon, & Hayes, 2017 ). Substance use disorders and other mental illnesses that are associated with trauma (e.g., posttraumatic stress disorder, major depressive disorder, personality disorders) are particularly common (Fazel & Danesh, 2002 ; Fazel et al, 2017 ; Karlsson & Zielinski, 2020 ). Beyond the obvious personal health implications of mental illness, it can also contribute directly to the outcomes that incarceration is supposed to deter.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Incarcerated women are also a highly traumatized population resulting in the need for increased specialised health needs. [5] It is crucial that all women within the prison sys-tem and wider communities have access to health services to assist in their overall health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%